2009
DOI: 10.1111/j.1529-8019.2009.01258.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there truly a risk of lymphoma from biologic therapies?

Abstract: The treatment of psoriasis has undergone a revolution with the advent of biologic therapies, including infliximab, etanercept, adalimumab, efalizumab, and alefacept. Biologics are generally safe and well tolerated. However, there has been concern over the risk of lymphoma with use of these agents due to their immunosuppressive properties. This review summarizes the current evidence in regards to lymphoma risk with biologic therapy obtained from case reports and case series, observational studies, clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 80 publications
3
34
0
Order By: Relevance
“…The other manifestations included infiltrative nodules and plaques (n = 5), eczematous changes (n = 1) and hypopigmented patches (n = 1). According to recent research, 34 lymphomas were associated with biological therapy in 2009, while 81 were detected in 2011 [23,24]. Specifically, the study from 2009 reported 2 cases (2.7%) of cutaneous T-cell lymphoma, 15 (20%) of B-cell non-Hodgkin lymphoma and 29 (38.7%) of T-cell lymphoma [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other manifestations included infiltrative nodules and plaques (n = 5), eczematous changes (n = 1) and hypopigmented patches (n = 1). According to recent research, 34 lymphomas were associated with biological therapy in 2009, while 81 were detected in 2011 [23,24]. Specifically, the study from 2009 reported 2 cases (2.7%) of cutaneous T-cell lymphoma, 15 (20%) of B-cell non-Hodgkin lymphoma and 29 (38.7%) of T-cell lymphoma [24].…”
Section: Discussionmentioning
confidence: 99%
“…According to recent research, 34 lymphomas were associated with biological therapy in 2009, while 81 were detected in 2011 [23,24]. Specifically, the study from 2009 reported 2 cases (2.7%) of cutaneous T-cell lymphoma, 15 (20%) of B-cell non-Hodgkin lymphoma and 29 (38.7%) of T-cell lymphoma [24]. Conversely, the data from 2011 showed 29 cases (35.8%) of B- cell non-Hodgkin lymphoma and 31 cases (38.3%) of T/natural killer cell non-Hodgkin lymphoma [23].…”
Section: Discussionmentioning
confidence: 99%
“…7 Biologics do not seem to be associated with an increased risk of cancer overall among patients with rheumatoid arthritis, 8,9 although there may be a slight increase in the risk of skin cancers. 10,11 Whether biologic use increases the risk of lymphoma beyond that associated with rheumatoid arthritis is controversial; 5,11,12 major limitations of the current data are lack of long-term follow-up and the need for very large samples because of the rarity of this event.…”
Section: What Adverse Effects Can Occur With Biologics?mentioning
confidence: 99%
“…36,55,57 However, when meta-analyses of these randomized controlled trials were considered, most of the patients who populated the original trials were from cohorts with rheumatoid arthritis and Crohn's disease, which usually combined biological therapies with additional immunosuppressive agents, therefore introducing selection bias and confounding. 61 In the absence of TNF-␣ blocking therapy, patients with moderate to severe rheumatoid arthritis, for example, have a 5-to 25-fold increased risk of developing lymphoma. 57 It is therefore unclear whether the increases in the rate of lymphoma observed in these trials were related to TNF-␣ blocking therapy.…”
Section: Screening Before Administration Of Biologic Therapymentioning
confidence: 99%